DIAGNOSIS OF ANIMAL BRUCELLOSIS BY ENZYME-LINKED IMMUNOSORBENT ASSAY (ELISA) METHOD - B.R.Kokilov (Western European Studies, 2025)
In the Turg'unboy Shokirov livestock-specialized farming enterprise located in Asaka district of Andijan region, a total of 158 out of 750 cattle were tested for brucellosis using the ELISA (Enzyme-Linked Immunosorbent Assay) method. As a result, 23 blood samples tested positive, while 128 samples were found to be negative. Seven blood samples were hemolyzed and deemed unsuitable for testing
Keywords: cattle; infection; brucellosis